Perfil da mortalidade por suicídio em idosos no Brasil: uma análise das diferenças entre os gêneros - Azevedo, Ulicélia Nascimento de (2018)
The objective of this study was to analyze the suicide mortality in the elderly in the Brazilian states between 2007 and 2016, considering the differences between the male and female genders. This is an ecological study that analyzed the suicide mortality of individuals aged 60 and over that occurred in the period from January 1, 2007 to December 31, 2016 in the 26 states and the Federal District of Brazil. Deaths categorized from the International Statistical Classification of Diseases and Related Health Problems - 10th Revision (Intentional Selfharm: X60-X84) were used. The source of death information was the Mortality Information System (SIM). There were 15,966 suicide deaths in the elderly in Brazil in the period from 2007 to 2016, with a proportion of 81% (12,923) for males and 19% (3,043) for females. The main cause of death was intentionally self-inflicted injury by hanging, strangulation and suffocation with a proportion of 65.94% and 54.03% for men and women, respectively. In both sexes, suicide mortality occurred mainly among married couples, the most prevalent place of suicide was the household, among white / race individuals. The trend shows that the mortality rate by regions of Brazil for both sexes presents similar behavior for all the years of the series from 2007 to 2016. The temporal analysis of the mortality by suicide of the elderly in Brazil in the studied period presents a prominent male overmortality for the South and Center-West regions. Descriptive statistics also show a higher mean for males (28.73) than for females (5.45) throughout the analyzed period. The spatial distribution of the Standardized Mortality Rate (TMP) by suicide according to sex in Brazil indicated a rate of 6.29 deaths per 100.000 inhabitants for both sexes, for the male sex of 28.14 deaths and for the female rate of 5.24 deaths, both per 100.000 inhabitants. The highest average rates of suicide mortality were for Rio Grande do Sul (both sexes with 15.10, men with 69.50 and women with 12.08), Santa Catarina (both sexes with 12.83, men with 56.59 and female with 10.61) and Piauí (both sexes with 11.23, male with 47.51 and female with 11.50). It is concluded that the differences in mortality due to suicide in the elderly in Brazil occur mainly in quantitative terms, with a higher prevalence in the male group. It presents a tendency of increase in both sexes and disparities in its spatial distribution. As for the qualitative aspects, it can be observed, through the analysis of the results found and the available literature, that age, marital status, race and socio-cultural differences exist, differences in the choice of methods for suicide and the motivations that result in the suicide act, can configure differences between the genders in the occurrence of suicide in the elderly population. Further studies are needed with an emphasis on the analysis of these differences to strengthen these observations and their evidence.